Accounting for research quality: Research audits and the journal rankings debate. (February 2015) - Rowlinson, Michael; Harvey, Charles; Kelly, Aidan; Morris, Huw; Todeva, Emanuela
Abstract: The question of whether and how research quality should be measured, and the consequences of research audits such as the UK's Research Excellence Framework (REF) – formerly the RAE – are considered in relation to the role of journal ratings such as the Association of Business Schools Academic Journal Quality Guide (the ABS Guide ). Criticism of the ABS Guide has distracted attention from the results of successive RAEs, where the panel for Business and Management has been one of the most selective in its allocation of the highest grades, especially when compared with the neighbouring field of Economics. If the ABS Guide had been used to grade outputs submitted for Business and Management in the RAE 2008 then many more outputs would have received the highest grades, especially in accounting where outputs from journals such as Critical Perspectives on Accounting, which are highly rated in the ABS Guide, appear to have been downgraded by the RAE panel. The alleged bias against accounting in the ABS Guide rests on a particular interpretation of citation impact factors for journals, and a narrow definition of subject fields. Critics of the ABS Guide would be better advised to direct their attention to scrutinizing the results of the REF and considering whether it provides an adequate research ranking for UK business schools. 15% of all full time students in the UK study business and management, including accounting and finance, but only 6.7% of the full time equivalent research active staff submitted in the RAE 2008 were in business and management, or accounting and finance. Research audits are therefore forcing the separation of teaching from research in UK business schools. With an estimated ratio of 71 full time students per research active faculty member in UK business schools, it may be time to consider a more appropriate, inclusive, and economical form of ranking for research in business and management.